"Effects of legislature control over municipal administration - realities and desirabilities - Sahay, Brij Kishore
This paper has a distinct bearing on the legislative control over municipal administration, the most fundamental form of state control, which forms the significant aspect of Control and supervision over municipal administration. The author has tried to evaluate the existing system and various tools of Legislative control over municipal bodies and has illustrated through the examples of Bihar. The author has also made some suggestions for making the legislative control keeping in view the principles of democracy and local self government
Keywords: Municipal Government; Legislative Control; India; State - Municipal Relations - India